The Nanoparticle Size Effect in Graphene Cutting: A "Pac‐Man" Mechanism. Issue 34 (24th May 2016) - Qiu, Zongyang; Song, Li; Zhao, Jin; Li, Zhenyu; Yang, Jinlong
Abstract: Metal‐nanoparticle‐catalyzed cutting is a promising way to produce graphene nanostructures with smooth and well‐aligned edges. Using a multiscale simulation approach, we unambiguously identified a "Pac‐Man" cutting mechanism, characterized by the metal nanoparticle "biting off" edge carbon atoms through a synergetic effect of multiple metal atoms. By comparing the reaction rates at different types of edge sites, we found that etching of an entire edge carbon row could be triggered by a single zigzag‐site etching event, which explains the puzzling linear dependence of the overall carbon‐atom etching rate on the nanoparticle surface area observed experimentally. With incorporation of the nanoparticle size effect, the mechanisms revealed herein open a new avenue to improve controllability in graphene cutting. Abstract : Surface or interface? By employing a multiscale simulation approach, a "Pac‐Man" mechanism is revealed for the nickel‐nanoparticle‐catalyzed cutting of graphene. Although the overall cutting rate is proportional to the surface area of the nanoparticle, it is found that the rate‐limiting step is actually at the graphene–metal interface instead of on the nanoparticle surface.